Inovasi Bantul Seroja (Sehat Ekonomi Meningkat Karo Jamu) - Nabila Septia Rosa; Bintoro Wardiyanto (Public Administration Dept, Faculty of Social and Political Science, 2024)
Bantul Seroja Program is a breakthrough innovation launched by the Bantul Regency Government to integrate traditional and conventional health services amid the disruption of the COVID-19 pandemic. This program succeeded in placing Bantul Regency in the top 45 public service innovations of Kemenpan-RB in 2022. By carrying out the New Public Governance paradigm, this program involves collaboration between the government, MSMEs, and the community in making and marketing traditional herbal medicine. This research uses a qualitative method of literature study, using secondary data sources obtained from books, supporting articles, scientific papers, previous studies and other literature.Despite facing challenges in resource availability and the need for product diversification, Bantul Seroja has shown significant improvements in the quality of health services and local economic welfare. Recommendations to strengthen the program include improved coordination across sectors, development of a wider network, and more optimal utilization of resources. With these measures, Bantul Seroja is not only able to respond to the challenges of the pandemic but also encourage sustainability and inclusiveness in local governance. This program is a model for implementing New Public Governance that is effective in overcoming crises and improving the quality of life of the community.